Performance of different digital elevation model resolution for the Rompin River Basin - Amirul Naqiuddin Jamaludin, Jamaludin (2019)
Digital elevation model (DEM) of a watershed forms key basis for hydrologic modelling and its resolution plays a key role in accurate prediction of various hydrological processes. This study appraises the effect of different DEMs with varied spatial resolutions namely 5m Interferometric Synthetic Aperture Radar (IFSAR) - Digital Terrain Model (DTM) and 30m Shuttle Radar Topography Mission (SRTM) - Digital Elevation Model (DEM) using ArcGIS software application for the case study of Rompin River Basin in Rompin, Pahang. The objectives of this study are to delineate river network and basin catchment, and to evaluate the performance of the 30m SRTM-DEM and 5m IFSAR-DTM in providing physical and topographical information for the Rompin river basin. From the result of the case study, it was observed that the different DEMs resolution produced different accuracies. The average error difference compared to the digitised river network for the 5m IFSAR-DTM was found out to be larger compared to the 30m SRTM-DEM. The large error was caused by the z-value assigned during the reconditioning process. Since the performance of 30m SRTM-DEM is close to the 5m IFSAR-DTM, it indicates that 30m resolution is sufficiently reliable in providing physical and topographical information of the Rompin River Basin.